Perkawinan Anak Dan Hak Anak: Analisis Pencegahan Dari Perspektif Positivisme - Qoyyima, Azrotul; Pradayani, Santi; Utami Wahyuningati, Syarifah Tri; Rato, Dominikus (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2025)
The prevalence of child marriage in Bondowoso Regency persists despite the existence of legal restrictions on the minimum age for marriage. This practice not only violates children's rights but also leads to various negative consequences.The formulation of issues in this research are: (1) What are the contributing factors to the high incidence of child marriage in Bondowoso Regency? (2) How does the positivist paradigm perceive the prevention of child marriage in Bondowoso Regency? This study employs a socio-legal method, combining legislative and conceptual approach. Primary data were obtained through interviews, while secondary data were collected from various literature reviews. The findings indicate that both internal and external factors contribute to the high rate of child marriage in the Bondowoso regency. From the positivist perspective, the Bondowoso Regency Government has undertaken preventive measures through legal and non-legal aspects. The study concludes that these efforts have shown positive outcomes; ; however, the involvement of all parties through collaborative governance is needed to implement comprehensive and sustainable child marriage prevention as a manifestation of the commitment to uphold children's rights.